Synthesis of N4‐Methylcytidine (m4C) and N4, N4‐Dimethylcytidine (m42C) Modified RNA. Issue 9 (16th September 2021) - Zheng, Ya Ying; Mao, Song; Sheng, Jia
Abstract: This article summarizes the protocols for phosphoramidite chemistry and solid phase synthesis of RNA oligonucleotides containing N 4 ‐methylcytidine (m 4 C) and N 4, N 4 ‐ dimethylcytidine (m 4 2 C) residues for base‐pairing, structural, and enzymatic activity studies. The two key m 4 C and m 4 2 C phosphoramidite building blocks can be synthesized starting from the partially protected cytidine nucleosides, followed by solid‐phase synthesis and HPLC purification of the modified target RNA oligonucleotides. These modified RNA strands are then prepared for base pairing stability, specificity, and structural studies using UV‐melting temperature ( T m ) measurements and X‐ray crystallography. Functional studies are performed by reverse transcription assays in primer extension reactions employing different enzymes. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Chemical synthesis of m 4 C phosphoramidite Basic Protocol 2 : Synthesis of m 4 2 C phosphoramidite Basic Protocol 3 : Synthesis and purification of m 4 C and m 4 2 C containing RNA oligonucleotides